Pancreatic adenocarcinoma in a Sri Lankan patient with neurofibromatosis 1 - Nitharshan, T.; Kumanan, T.; Sirisena, N. D.; Anandagoda, G.; Dissanayake, V.H.W.; Navaneethakrishnan, S.; Sujanitha, V.; Sutharhan, V.; Mathangi, N. (Sri Lanka Journal of Medicine, 2023)
A 27-year-old Sri Lankan man with Neurofibromatosis-1 (NF-1) [MIM:162200] who presented with vague abdominal pain associated with loss of weight and appetite for 1-year duration is described. He had multiple cutaneous neurofibromas, café-au-lait macules and bilateral Lisch nodules. An abdominal contrast-enhanced computed tomography scan showed a mass lesion in the retro pancreatic region with mild enhancement. Diagnostic laparotomy showed multiple liver metastases. Liver biopsy showed an immune morphology which is compatible with deposits of ck17 and ck19 weakly positive adenocarcinoma which led to the probable diagnosis of a pancreatic carcinoma. Genetic testing identified a germline heterozygous pathogenic variant in exon 12 of the NF-1 gene [NM_001042492.3: c.1307C>A]. The substitution creates a nonsense variant at codon position 436, which changes a Serine to a premature stop codon in the NF-1 protein [NP_001035957.1: p. Ser436Ter]. Patients diagnosed with NF-1 may rarely develop malignancies including pancreatic neuroendocrine tumors and pancreatic adenocarcinomas.
Keywords: Neurofibromatosis-1; Neuroendocrine tumor; Pancreatic adenocarcinoma; Von Recklinghausen’s syndrome